Fair Flow Control in Solar Powered WLAN Mesh Networks - Badawy, G.H.; Sayegh, A.A.; Todd, T.D. (2009 IEEE Wireless Communications and Networking Conference, 2009)
Wireless LAN mesh networks are used to provide Wi-Fi access for temporary events. In this type of application it is sometimes necessary to operate some of the mesh nodes using an energy sustainable source, such as solar power. When the network is deployed, each mesh node is equipped with a solar panel and battery combination which is sufficient to prevent network outage using an assumed traffic design profile. During post-deployment network operation however, the actual traffic flows may be different from that for which the nodes were originally provisioned. To prevent node outage, the network must flow control the inputs, and this should be done in as fair a manner as possible. In this paper we propose a mechanism for achieving fair flow control on a per-flow basis. We first formulate a bound which achieves the best max-min fair flow control subject to eliminating network outage. This bound is non-causal in that it uses knowledge of future solar insolation and traffic flows to determine the optimum flow control. The bound motivates a proposed causal flow control algorithm whose operation uses prediction based on access to on-line historical weather data. Our results show that the proposed algorithm eliminates node outage and performs very well compared to the optimum flow control bound for a variety of network scenarios.